Efektivitas Metode Ceramah Berbantu Quiziz Tingkatkan Hasil Belajar Siswa SMPIT Harapan Umat - Ady Prasetyo Ryan Nugroho; Danuwangsa Kusuma; Ilham Muhamad Yasin; Lulu Mala Bonita; Muhamad Sulthan Sauri; Khalid Ramdhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to analyze the effectiveness of the lecture teaching method integrated with the interactive learning technology Quizizz in improving student learning outcomes. The problem being discussed is the results of interaction and student learning outcomes using conventional teaching methods. This study used a quasi-experimental method with a pretest-posttest design on two groups, namely the experimental group using the lecture method with Quizizz and the control group using the traditional lecture method without the use of technology. The data collection instrument was the learning outcomes given before and in accordance with the work being done. The results of the analysis showed a significant increase in learning outcomes in the experimental group compared to the control group. shows that the use of Quizizz as an interactive learning tool can increase the effectiveness of the lecture method, encourage student participation, and have a positive impact on learning outcomes. Therefore, the use of technology such as Quizizz can be an alternative solution to overcome the shortcomings of conventional lecture methods.